A fatal case of Ecthyma Gangrenosum in a critically ill and immunocompromised patient - Tomanovic, Marija; Reljic, Vesna; Peric, Jelena; Zivanovic, Dubravka (The Journal of Infection in Developing Countries, 2023)
Introduction: This brief picture-oriented case report focuses on typical skin lesions in a patient who developed Ecthyma gangrenosum and pseudomonal sepsis after extensive immunosuppressive therapy for Pemphigus vulgaris. Case presentation: The patient was immunosuppressed with high doses of glucocorticoids and azathioprine; the follow-up after the treatment was not carried out well due to the pandemic conditions and because the patient herself got a Covid infection, which resulted in the development of pseudomonal sepsis and Ecthyma gangrenosum. The outcome was fatal despite extensive broad-spectrum antibiotic therapy, plasmapheresis, and intravenous immunoglobulins. Conclusions: Infections with Pseudomonas aeruginosa have become a real concern in hospital-acquired infections, especially in critically ill and immunocompromised patients, because of multi-drug resistance in the first place.